Does a new tax system have an economic impact on a forest investment? - Aschan, Wilhelm (SLU/Dept. of Economics, 2015)
The Swedish forest owners own more than half of the productive forest land in Sweden. Interest in investing in forestry has increased in recent years which are reflected in price developments in forest land over the last 10 years. Businesses engaged in forestry are often operated as a private firm. The Swedish legislation allows only a few exceptional cases owning forest land in share holding companies. This means that income from forestry for individuals today is usually taxed as work-incomes where the tax scale is progressive. The largest income post in a private firm engaged in forestry is cutting payments. The two deciding factors when a person chooses to do a final cut is the current timber prices and details from the forest management plan when the forest is mature enough to be cut. Timber prices have varied over the years, and the age distribution of the forest for the firm owner is usually uneven. This means that final cutting is concentrated in only a few years over a 20 year period. That in turn means large variations annually regarding payments from the forest for the forest manager. To even out the concentrated payments, the individual firm owner currently has several opportunities to defer income over time, to get a uniform and fair taxation. It is by means of forest account, reservation for allocation fund, funds retained for expansion and interest adjustment for self-employment. Currently, there is a tax proposal about changing the rules concerning the ability to allocate surplus in a private firm. The tax proposal would remove forest account, tax allocation fund and funds retained for expansion and replace them with a business fund, and meanwhile the rules regarding interest distribution changes. The business fund implies only 40% of the annual surplus can be allocated, resulting in a larger portion will be taxed annually in the progressive tax system. The study includes two fictive forest buyers that, based on a literature review intend to represent the Swedish forest owner. One forest management plan is the basis for all the forest estimates. The study compares the results of a forest investment for the two different owners with regard to whether the existing or proposed tax is applied. In order to obtain comparable results a simulation model was developed based on theoretical grounds around the topic, literature written about the problem as well as assumptions based on actual forecasts and data. The results show that the most crucial factors for the investment’s profit is the level of interest rates and price development of forest properties. Revised tax ratios are marginal in this context. The prevailing tax conditions have an effect on how large surplus that can be reinvested in the business. The results show that the existing system is more advantageous when applying the new proposal, it is more beneficial for the owner to make regular withdrawals from the forest.